SAT0386 What is the Best Screening Test to Identify Lupus Patients with Cognitive Impairment in an Ambulatory Setting?. (9th June 2015) - Nantes, S.; Urowitz, M.; Gladman, D.; Su, J.; Dhaliwal, A.; Touma, Z.
Abstract : Background: Late stage cognitive impairment is increasingly recognized in patients with systemic lupus erythematosus (SLE). Yet there is an unmet need for a clinical assessment of cognitive function that can be administered in an ambulatory setting. Objectives: To determine: 1) the validity of the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) as screening tests of Cognitive Impairment (CI) in SLE and 2) associated factors with CI. Methods: Consecutive patients with SLE visiting the Toronto Lupus Clinic since Feb 2014 that agreed to participate in all study's phases were included. Patients underwent the battery of cognitive screening tests administered by 2 trained assessors: Hopkins Verbal Learning Test-Revised (HVLT-R) and Controlled Oral Word Association Test (COWAT) via telephone interview and MoCA and MMSE via face-to-face assessment. Patients completed the Perceived Deficits Questionnaire – 5-item (PDQ-5). Sensitivity (Se)/specificity (Sp) of MoCA and MMSE in detecting CI (HVLT-R external construct) were determined. Pearson correlation of MoCA and MMSE with HVLT-R and COWAT, were studied. PDQ-5 scores were compared in patients with and without CI. Center of Epidemiologic Studies Depression Scale (CES-D), Beck Anxiety Inventory (BAI), and Reynolds Intellectual Screening Test (RIST) were completed by patients. Logistic regression analyses were performed to test for possible associations with CI. Results: 73 patients participated; 92% female, mean age 48±13 years, lupus disease duration 18±12 years, and SLE Disease Activity Index 2000 (SLEDAI-2K) 3.7±4.1. Prevalence of CI: 47% had CI using MoCA, 40% using HVLT-R, 16% using COWAT and 14% using MMSE. Patients with CI had marked impairment in attention, language and delayed recall in the domains of MoCA compared to normal controls (Table 1 ). Se/Sp: Sensitivity was higher for MoCA (69%) compared to MMSE (21%), though MMSE was more specific (91%) than MoCA (68%). Correlation: HVLT-R correlated with MoCA (r=0.43, p=0.0001). PDQ-5 showed higher scores in CI patients compared to patients without CI (10.16±4.60 vs. 8.41±3.95, p=0.11) [higher scores = greater perceived impairment]. Association: There was no significant difference in CES-D, BAI or RIST scores between patients with and without CI. The following variables were analyzed one by one univariate regressions for the outcome of cognitive impairment: age, sex, age at diagnosis, lupus disease duration, education years, SLEDAI-2K, CES, BAI and RIST (variables with p<0.2 were entered into multivariate logistic regression). Patients with CI had a shorter lupus disease duration (14.8±9.6 yr) compared to patients without CI (20.6±12.6 yr) (p=0.037) but although there was a trend of being statistically significant (p=0.06), this did not hold in the multivariate analysis. High intelligence score is protective against CI (OR=0.9; CI 95% 0.86-0.99; P=0.02) and each 1-point increase in RIST decreases the chance of developing CI by 7.3%. Conclusions: CI among SLE patients was highly prevalent (47%) in this study using MoCA. Ease of use and time needed for an assessment, make the MoCA the preferential screening test for CI in patients with SLE compared to HTLV-R. Low intelligence scores were associated with CI but depression and anxiety were not. Disclosure of Interest: None declared